Experimental Study on Lateral Permeability Evolution of Sandstone under Seepage-Damage Coupling - Dongdong Pang; Feisheng Feng; Guanghui Jiang; Dongjing Xu; Xiaohan Wang (Advances in Civil Engineering)
To analyze the internal pore evolution law of aquifer rock in a coal mining front under the coupling effect of stress and seepage and the influence on the water inrush performance of the working face, research on the working face was conducted to improve the RTR-1000 high-temperature and high-pressure rock triaxial mechanical testing system, using hollow cylindrical and complete sandstone samples and by considering the stress change law in the actual mining process as the reference loading path. At the initial stage of loading, the permeability of sandstone demonstrates a rapid downward trend within a small range of stress change, with a decline rate of 50%. At lower permeabilities, the fluctuation is small; the plastic and failure stages are transient, and the relationship curve between the horizontal permeability and the axial confining pressure of sandstone is divided into compaction, multiple fluctuations, surrender, and failure. In several stages, the sandstone lateral permeability experiment under the coupling effect of stress and seepage demonstrates that the permeability of the aquifer in the coal mining front is significantly reduced after the original rock stress is disturbed by mining, suggesting that the water inrush calculation of the traditional water-flowing fractured zone and caving zone aquifer rock permeability experiment is inaccurate. Further research can deepen the stress and seepage coupling evolution process under the action of working face water inrush.